2012
DOI: 10.1186/1756-0500-5-617
|View full text |Cite
|
Sign up to set email alerts
|

Lung Cancer Signature Biomarkers: tissue specific semantic similarity based clustering of Digital Differential Display (DDD) data

Abstract: BackgroundThe tissue-specific Unigene Sets derived from more than one million expressed sequence tags (ESTs) in the NCBI, GenBank database offers a platform for identifying significantly and differentially expressed tissue-specific genes by in-silico methods. Digital differential display (DDD) rapidly creates transcription profiles based on EST comparisons and numerically calculates, as a fraction of the pool of ESTs, the relative sequence abundance of known and novel genes. However, the process of identifying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 64 publications
2
31
0
Order By: Relevance
“…We observe down-regulation of CK1α and PP2A in no-ductal carcinoma patients, suggesting a different molecular signature in blood for each breast cancer histological type. Consistent with priors studies, CK1α showed decrease expression in lung carcinoma cells, indicating that it may be involved in carcinogenesis process (Xie et al, 2003;Srivastava et al, 2012) and PP2A was down-regulated in clear cell renal cell carcinoma and prostatic cancer. The authors found PP2A decreased expression associated with cancer risk (Westermarck and Hahn, 2008;Li et al, 2014).…”
Section: Discussionsupporting
confidence: 74%
“…We observe down-regulation of CK1α and PP2A in no-ductal carcinoma patients, suggesting a different molecular signature in blood for each breast cancer histological type. Consistent with priors studies, CK1α showed decrease expression in lung carcinoma cells, indicating that it may be involved in carcinogenesis process (Xie et al, 2003;Srivastava et al, 2012) and PP2A was down-regulated in clear cell renal cell carcinoma and prostatic cancer. The authors found PP2A decreased expression associated with cancer risk (Westermarck and Hahn, 2008;Li et al, 2014).…”
Section: Discussionsupporting
confidence: 74%
“…Studies have shown that Nampt is significantly increased in primary colorectal cancer [5], [6], [7] and other cancers [8], [9], [10], [11]. Thus, Nampt may be a good biomarker of malignant potential and stage progression [1], [8], [25], [26].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Nampt may be a good biomarker of malignant potential and stage progression [1], [8], [25], [26]. Nampt-mediated NAD biosynthesis plays a critical role in cell metabolism, survival functions, and stress resistance through sirtuins and other NAD-consuming regulators [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, those types of predictions were based on computational approaches not involving NGS, such as microarray analysis, qPCR, and others [6][7] [8] in various types of cancer such as colorectal [9], lung [10], prostate [11], breast cancer [12] and others.…”
mentioning
confidence: 99%